Antioxidant content activity and nitric oxide scavenging ability of Ilex guayusa compared with Camellia sinensis and Aspalathus linearis tea - Bester, Megan J. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.